. Which of the following is the vertex form of the expression below?
y = 6x2 - 36x + 58
A. y = 6(x - 3)2 + 4
B. y = 6(x - 3)2 + 112
C. y = 6(x - 3)2 + 58
D. y = 6(x + 3)2 + 4

. Which of the following is the vertex form of the expression below?
y = 6x2 - 36x + 58
A. y = 6(x - 3)2 + 4
B. y = 6(x - 3)2 + 112
C. y = 6(x - 3)2 + 58
D. y = 6(x + 3)2 + 4

The following that is the vertex form of the expression y = 6x^2 - 36x + 58 is: A. y = 6(x - 3)^2 + 4. y = 6x^2 - 36x + 58 y = 6x^2 - 36x + 54 + 4 y = 6(x^2 - 6x + 9) + 4 y = 6(x - 3)^2 + 4

. Which of the following is the vertex form of the expression below? y = 6x2 - 36x + 58 A. y = 6(x - 3)2 + 4 B. y = 6(x - 3)2 + 112 C. y = 6(x - 3)2 + 58 D. y = 6(x + 3)2 + 4

The following that is the vertex form of the expression y = 6x^2 - 36x + 58 is: A. y = 6(x - 3)^2 + 4. y = 6x^2 - 36x + 58 y = 6x^2 - 36x + 54 + 4 y = 6(x^2 - 6x + 9) + 4 y = 6(x - 3)^2 + 4

Weegy: x2 - x - 90 = 0 in factored form is (x-10)(x+9)=0 User: Solve for x in the following equation.
x2 - 10x + 16 = 0
A. x = -2; -8
B. x = 1; 16
C. x = 2; 8
D. x = 5; 5
(More)

There are no comments.